Effects of hospital care environment on patient mortality and nurse outcomes - Aiken, Linda H; Clarke, Sean P; Sloane, Douglas M; Lake, Eileen T; Cheney, Timothy (The Journal of nursing administration, 2009)
The objective of this study was to analyze the net effects of nurse practice environments on nurse and patient outcomes after accounting for nurse staffing and education. Staffing and education have well-documented associations with patient outcomes, but evidence on the effect of care environments on outcomes has been more limited. Data from 10,184 nurses and 232,342 surgical patients in 168 Pennsylvania hospitals were analyzed. Care environments were measured using the practice environment scales of the Nursing Work Index. Outcomes included nurse job satisfaction, burnout, intent to leave, and reports of quality of care, as well as mortality and failure to rescue in patients. Nurses reported more positive job experiences and fewer concerns with care quality, and patients had significantly lower risks of death and failure to rescue in hospitals with better care environments. Care environment elements must be optimized alongside nurse staffing and education to achieve high quality of care.